The impact of perceptions of China’s human rights and sustainable development on its soft power initiatives in South Africa - Calitz, Willemien (Centre for Film and Media Studies, 2020)
This study examined the representation of China’s human rights and sustainability record in the mainstream South African media. It also explored the factors that influence both South African and Chinese journalists and its potential effects on their coverage of China’s sustainable development and human rights impact. Through its “Going Out” policy, China has re-established a close affiliation with African countries.. South Africa is significant to this growing China-Africa relationship, as a fellow member of the BRICS group of emerging nations. Through its soft power strategy, whether as a “charm offensive” (Kurlantzick, 2008), or “charm defensive” (Shi, 2013), China has expanded its media reach in Africa through platforms such as Xinhua, China Central Television (CCTV) and People’s Daily to provide counter stereotypical images of being “a mysterious, exotic and unknowable force” (Wasserman, 2012). Dominant media discourses have represented China as lacking concern for good governance, transparency, freedom of the press, worker’s rights, human rights, and environmental protection in its relationship with Africa (Sautman & Hairong, 2009; French, 2014). China has been criticised for exporting its environmental destruction and human rights violations to the African continent. These negative perceptions among global media and key roleplayers could harm China’s strategies to harness its soft power on the African continent. This study explored to what extent these perceptions are manifested in media coverage, and what factors influenced this coverage. Through a qualitative framing analysis, this study examined how China’s sustainable development and human rights record is depicted in South African media. The framing analysis explored three individually-owned South African media publications: the weekly investigative paper Mail & Guardian, the Cape Times daily and the online news site News 24, to determine South African media representation of China. The study found five dominant frames in South African media’s coverage of China’s sustainable development record. China as key perpetrator in poaching; China vs the USA as a superpower; China’s role in the struggle against climate change; China as a source of green technologies, renewable energy and green investment; and China as a polluted country itself. Regarding South African media’s coverage of China’s human rights record, three dominant themes have emerged: Cheap Chinese products replacing job opportunities in Africa, China’s general poor record of human rights and cheap Chinese labour in African countries. Additionally five dominant frames were found in Chinese media coverage of China’s sustainable development: China’s climate leadership, China-US collaboration, repercussion for environmental violations, China’s green technology and innovation, pollution in China, and Chinese environmental aid. Regarding human rights, only three dominant frames were found: Chinese jobs empower African communities, improved labour conditions and official human rights engagements. The second part of this study examined how China’s media image might influence Chinese and South African journalists’ coverage of China’s sustainable development and human rights impact. Apart from China’s environmental and human rights reputation, which other influences on journalists have been significant to their coverage of China? Using Reese’s (2001; 2016) hierarchy of influences model as a guideline, this study explored the individual, routine, organisational, extra-media and ideological influences on Chinese and South African journalists covering China’s human rights and sustainable development reputation. Using semi-structured interviews, 20 journalists from Chinese and South African publications were interviewed. The interview questions built on Reese’s (2001; 2016) sociology of the media approach. The aim was to compare the different layers of how journalists in China and South Africa are influenced when covering China’s human rights and sustainable development record. Results show that South African journalists were strongly influenced by their perceptions of China’s environmental and human rights impact, which are generally pessimistic. They find Chinese government and sources to be inaccessible and distrust them. South African journalists also believe that media diplomacy will not lead to soft power success in Africa, in particular compared to efforts such as health diplomacy. Chinese journalists were strongly influenced by the Chinese state’s media ownership. Despite censorship, Chinese journalists find working for Chinese publications, Xinhua in particular, honourable. They find their role in improving China’s soft power in Africa through media diplomacy to be crucial, and particularly through challenging current western representations of China.